Factor VIIa-antithrombin complexes in patients with arterial and venous thrombosis - Spiezia, Luca; Rossetto, Valeria; Campello, Elena; Gavasso, Sabrina; Woodhams, Barry; Tormene, Daniela; Simioni, Paolo (Thrombosis and Haemostasis, 2010)
Antithrombin (AT), in the presence of heparin, is able to inhibit the catalytic activity of factor VIIa bound to tissue factor (TF) on cell surfaces. The clinical meaning of FVIIa-AT complexes plasma levels is unknown. It was the objective of this study to evaluate FVIIa-AT complexes in subjects with thrombosis. Factor VIIa-AT complexes plasma levels in 154 patients consecutively referred to our Department with arterial or venous thrombosis and in a group of 154 healthy subjects, were measured. Moreover, FVIIa-AT complexes were determined in: i) n = 53 subjects belonging to 10 families with inherited factor VII deficiency; ii) n = 58 subjects belonging to seven families with AT deficiency; iii) n = 49 patients undergoing oral anticoagulant therapy (OAT). Factor VIIaAT levels were determined by a specific ELISA kit (R&D, Diagnostica Stago, Gennevilliers, France). Factor VIIa-AT complexes mean plasma levels were lower in patients with either acute arterial (136 ± 40 pM) or venous (142 ± 53 pM) thrombosis than subjects with previous thrombosis (arterial 164 ± 33 pM and venous 172 ± 61 pM, respectively) and than healthy controls (156 ± 63 pM). Differences between acute and previous thrombosis, were statistically significant (p < 0.05). Subjects with inherited and acquired (under OAT) factor VII deficiency had statistically significant lower FVIIa-AT complexes plasma levels (80 ± 23 pM and 55 ± 22 pM, respectively) than controls (150 ± 51 pM, p < 0.0001 and 156 ± 63 pM, p < 0.00001, respectively). Factor VIIa-AT complexes are positively correlated with plasma factor VII/VIIa levels. Further investigations are needed to verify the possible role of higher FVIIa-AT complex plasma levels in predicting hypercoagulable states and thrombosis.
Keywords: Venous thrombosis; arterial thrombosis; factor VIIa/AT complexes